Siamese Network-Based All-Purpose-Tracker, a Model-Free Deep Learning Tool for Animal Behavioral Tracking - Su, Lihui; Wang, Wenyao; Sheng, Kaiwen; Liu, Xiaofei; Du, Kai; Tian, Yonghong; Ma, Lei (Frontiers in Behavioral Neuroscience, 2022)
Accurate tracking is the basis of behavioral analysis, an important research method in neuroscience and many other fields. However, currently available tracking methods have limitations. Traditional computer vision methods have problems in complex environments, and deep learning methods are hard to be applied universally due to the requirement of laborious annotations. To address the trade-off between accuracy and universality, we developed an easy-to-use tracking tool, Siamese Network based All-Purpose Tracker (SNAP-Tracker), a model-free tracking software built on the Siamese network. The pre-trained Siamese network offers SNAP-Tracker a remarkable feature extraction ability to keep tracking accuracy, and the model-free design makes it used directly before laborious annotations and network refinement. With an additional detection module, SNAP-Tracker provides a “tracking with detection” mode to keep stable performance when tracking long videos. We demonstrate the stability of SNAP-Tracker through different experimental conditions and different tracking tasks. In short, SNAP-Tracker provides a general solution to behavioral tracking without compromising accuracy. For the user’s convenience, we have integrated the tool into a tidy graphic user interface and opened the source code for downloading and using (https://github.com/slh0302/SNAP).